A training on excavator operator for Youth Organizations, Loa Jananilir District, Samarinda City - Darma Aviva; Abdul Halim; Abdul Halik; Aditya Putra Wibowo (Community Empowerment, 2021)
East Kalimantan is one of the provinces that has natural resources, especially the abundant mining sector such as coal, oil, and gas. The growth of the coal mining sector makes the level of heavy equipment use also increase. The purpose of this service is to improve the knowledge and skills of the community in the field of heavy equipment for youth organizations, Loa Jananilir District, Samarinda City, East Kalimantan. The service method is carried out by socializing for youth organizations. The results of the service show that there is an increase in public interest, especially young people, in heavy equipment, especially to support East Kalimantan which will become the new State Capital (Ibu Kota Negara/IKN). The use of excavator type heavy equipment can increase work efficiency and be more optimal because the area that can be worked on is wide and in a short time.